KOMPONEN UTAMA UNTUK PENGENDALIAN KUALITAS SECARA STATISTIK - Nurhasanah, Nunik; Safitri, Diah (Department of Statistics, Faculty of Science and Mathematics, Universitas Diponegoro, 2010)
Statistically Quality Control is a problem solving technique that used to check, control, analyze, bring off and repair product with statistical methods. One of the method that used statistically control quality is Principal Component Analysis. Principal Component Analysis is a multivariate technique that used to reduce the dimension of data. Principal component is concerned with explaining the variance-covariance structure of a set of variables through a few linear combinations of these variables. Statistically quality control with principal components is used by constructing multivariate control charts which consist of Ellipse Chart for first two principal components and Â Chart for unexplained principal components in Ellipse Chart. Â Keywords : Principal Component Analysis, Ellipse Chart, Â Chart